RPE-derived exosomes rescue the photoreceptors during retina degeneration: an intraocular approach to deliver exosomes into the subretinal space - Yange Wang; Qian Zhang; Guoqing Yang; Yuanmeng Wei; Miao Li; Enming Du; Haijun Li; Zongming Song; Ye Tao (Taylor & Francis Group, 2021)
Retinal degeneration (RD) refers to a group of blinding retinopathies leading to the progressive photoreceptor demise and vision loss. Treatments against this debilitating disease are urgently needed. Intraocular delivery of exosomes represents an innovative therapeutic strategy against RD. In this study, we aimed to determine whether the subretinal delivery of RPE-derived exosomes (RPE-Exos) can prevent the photoreceptor death in RD. RD was induced in C57BL6 mice by MNU administration. These MNU administered mice received a single subretinal injection of RPE-Exos. Two weeks later, the RPE-Exos induced effects were evaluated via functional, morphological, and behavior examinations. Subretinal delivery of RPE-Exos efficiently ameliorates the visual function impairments, and alleviated the structural damages in the retina of MNU administered mice. Moreover, RPE-Exos exert beneficial effects on the electrical response of the inner retinal circuits. Treatment with RPE-Exos suppressed the expression levels of inflammatory factors, and mitigated the oxidative damage, indicating that subretinal delivery of RPE-Exos constructed a cytoprotective microenvironment in the retina of MNU administered mice. Our data suggest that RPE-Exos have therapeutic effects against the visual impairments and photoreceptor death. These findings will enrich our knowledge of RPE-Exos, and highlight the discovery of a promising medication for RD.